Exit theater - Lala, Mike, 1987- (Colorado Prize for Poetry., 2016)
Selected by Tyrone Williams for the 2016 Colorado Prize for Poetry, Exit Theater casts classical elegy, with dazzling formal innovation, into a staggering work of contemporary, political polyphony. Through monologues, performance scripts, and poems of exquisite prosody, Mike Lala examines the human figure--as subject and object, enemy and ally--in the context of a progressively de-figured and hostile world. Catullus, Shakespeare, Cy Twombly, and Lydia Delectorskaya echo across engagements with Israeli generals, accused terrorists, State Department employees, nuclear scientists, Saturday Night Live actors, war criminals, malware, and a host of mythic, literary, and half-extant spectral characters. Amid the cacophony, Lala implicates every actor, including himself, in a web of shared culpability vis-a-vis consumerism, representation, speaking, writing, and making art against the backdrop of the endless, open wars of a post-Cold War, post-2001 era. Exit Theater is a debut of and against its time--a book about war, art, and what it means to make art in a time of war.